Are competitive effect and response two sides of the same coin, or fundamentally different? - Wang, Ping; Stieglitz,Tara; Zhou, Dao Wei; Cahill Jr, James F. (My University, 2010)
1. The ability to suppress neighbour growth and the ability to withstand growth suppression are widely viewed as two forms of competition, competitive effect and competitive response. 2. We conducted a greenhouse experiment to determine whether these two forms of competition were functionally linked, and to determine which plant traits are associated with effect and response competitive abilities among seedlings of 22 perennial North American prairie species. We further explored the trait-function relationship by growing plants under different soil fertilities and with different neighbour species. 3. To determine competitive abilities, we used a phytometer approach with two phytometer species: Poa pratensis and Achillea millefolium grown in competition with each of the 22 focal species under low and high fertility. Root and shoot morphological traits were measured and principal component analyses were used to reduce the dimensionality of the data. Three axes were extracted, which roughly corresponded to size, root and shoot architecture. 4. The hierarchy of competitive effect ability of the target species did not vary with either soil fertility or neighbour identity, while the hierarchies of competitive response abilities were highly variable among the treatments. Competitive effect ability was closely associated with size-related traits under high nutrient conditions, and with root-related traits under low nutrient conditions. In contrast, few plant traits axes were related to competitive response. 5. These findings indicate significant differences between competitive effect and response ability. We suggest competitive effect ability is a consistent trait of a species, linked to specific plant traits. In contrast, we found little evidence to support the idea that competitive response ability is itself a species trait, and instead it appears this may be simply a collection of different ways of avoiding or tolerating competition and/or low nutrient conditions. Supporting this argument was a lack of any consistency in which traits were associated with competitive response ability. 6. We recognize the limitations of a single study of seedlings under greenhouse conditions. However, we suggest these findings indicate a need to critically examine current assumptions about plant competition, how it is defined, and the traits which control a species’ competitive ability.
Keywords: comparative study; competitive effect; competitive response; functional geology; plant competition; plant traits; soil fertility